Technical Maintenance Procedures for X-Ray Technology - Makhamadjon kizi, Rakhmatillayeva Mubina; Abdumukhtarovich, Gulamov Shukhrat (Journal of Science in Medicine and Life, 2025)
This article examines the technical maintenance procedures for X-ray technology, focusing on ensuring the quality and safety of X-ray equipment. The study highlights the importance of regular maintenance, diagnostic accuracy, and radiation safety. Furthermore, it provides an overview of the requirements for high-quality X-ray machine operation, discusses common challenges, and offers recommendations for improving maintenance procedures. This research is valuable for specialists working with radiology equipment and aims to enhance the efficiency and reliability of X-ray devices.